The Mayan in the Mall : Globalization, Development, and the Making of Modern Guatemala - Way, John T. (John Thomas), 1966- (Book collections on Project MUSE., 2012)
This twentieth-century history of Guatemala begins with an analysis of the Grand Tikal Futura, a postmodern shopping mall with a faux-Mayan facade that is surrounded by a landscape of gated subdivisions, evangelical churches, motels, Kaqchikel-speaking villages, and some of the most poverty-stricken ghettos in the hemisphere.